Low muscle mass and high visceral fat mass predict mortality in patients hospitalized with moderate-to-severe COVID-19: a prospective study. Issue 10 (26th September 2022) - Beltrão, Fabyan Esberard de Lima; Beltrão, Daniele Carvalhal de Almeida; Carvalhal, Giulia; Beltrão, Fabyo Napoleão de Lima; de Aquino, Igor Motta; Brito, Thaíse da Silva; Paulino, Barbara Costa; Aires, Elisa; Viegas, Diana; Hecht, Fabio; Halpern, Bruno; Pordeus, Liana Clebia De Morais; et al.
Abstract : Introduction: The severity of coronavirus disease 2019 (COVID-19) has been positively correlated with several comorbidities. The primary outcome of the study was to assess the relationship between the mortality and severity of COVID-19 and obesity classes according to BMI, visceral adipose tissue (VAT) area, s.c. adipose tissue area, muscle area (MA), and leptin levels. Methods: In this prospective cohort study, 200 patients hospitalized with moderate-to-severe COVID-19 underwent an unenhanced CT of the thorax and laboratory tests, and leptin levels between June and August 2020 were obtained. Results: Our study included 200 patients (male 52%; mean age: 62 (49–74) years; obesity (BMI > 30): 51.5%)). Fifty-eight patients (23.5%) were admitted to the intensive care unit and 29 (14.5%) died. In multivariate logistic regression (corrected for leptin, sex, age, and serum biomarkers) and receiver operating characteristic curve analyses, high VAT > 150 cm 2 (odds ratio (OR): 6.15; P < 0.002), MA < 92 cm 2 (OR: 7.94; P < 0.005), and VAT/MA ratio > 2 (OR: 13.9; P < 0.0001) were independent risk factors for mortality. Indeed, the Kaplan–Meier curves showed that patients with MA < 92 cm 2 and without obesity (BMI < 30) had a lower survival rate (hazard ratio between 3.89 and 9.66; P < 0.0006) than the other groups. Leptin levels were not related to mortality and severity. Conclusion: This prospective study reports data on the largest number of hospitalized severe COVID-19 patients and pinpoints VAT area and MA calculated by CT as predictors of COVID-19 mortality.